CLINICAL PRESENTATION AND OUTCOME OF TRAUMATIC EPIDURAL HEMATOMAS IN POSTERIOR FOSSA: STUDY OF 34 CASES - Haq, Naeem Ul; Azam, Farooq; Ishfaq, Muhammad; Khan, Bakht Zar; Jalal, Abdul (Journal of Postgraduate Medical Institute, 2016)
Objective: To determine the clinical presentation and outcome of traumatic epidural hematoma in posterior fossa. Methodology: This observational study was conducted in Department of Neurosurgery Lady Reading Hospital, Peshawar from 30th November 2009 to 29th November 2014. We collected data for both operated and non-operated cases of traumatic posterior fossa epidural hematoma, of any gender and age. Patients were followed for 6 months and all the data was analyzed by SPSS version 20 and presented in figures. Results: Total 34 patients were included in the study having age range from 5-60 years with mean age of 32.5±16.24 years. Males were 25(73.52%) and females were 9(26.47%). The most common cause was motor vehicle accident found in 15(44%) cases. seventeen (50%) patients were managed conservatively, while 17(50%) were managed by surgery. Good outcome was found in 28(82.35%) and in remaining 6(17.64%) there was poor outcome. Conclusion: The frequency of posterior fossa epidural hematoma was more in males. Motor vehicle accident was the most common cause in this study. Good outcome was found in a significant number of treated patients.